Peran Mediasi Orientasi Pasar Global Pada Pengaruh Human Capital Readiness Terhadap Kinerja Bisnis UMKM - Eva Yuniarti Utami; Ramadhani Kirana Putra; Jemadi; Yusniar; Afni Yeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the mediating role of global market orientation on the influence of human capital readiness on the performance of MSME businesses. The number of samples in this study was 64 MSME units. The method used in determining the sample in this study was the saturated sampling technique (census). The data collection method used in this study was interviews and surveys conducted by distributing questionnaires. This study uses a structural equation model SEM (Structural Equation Model) based on PLS (Partial Least Square). The results of this study indicate that human capital readiness has a positive and significant effect on business performance. Human capital readiness has a positive and significant effect on global market orientation. Global market orientation has a positive and significant effect on business performance. Global market orientation is able to mediate the effect of human capital readiness on business performance.